Complexities of Covishield Vaccine on COVID-Positive History Family in India after the Second (Booster) Dose - Parikshit Gautam Jamdade; Shrinivas Gautamrao Jamdade (Wolters Kluwer Medknow Publications, 2022)
COVID-19 epidemic severely affects the social life of people living in India. The best solution to the COVID-19 problem is the vaccination of the people. In India, COVID-19 vaccination started from January 16, 2021, mainly with the Covishield vaccine. In this study, the COVID-positive history family was selected who had taken the first and second (booster) doses residing at Pune, Maharashtra, India, was followed up to check for any side effects postvaccination. Their data were collected with participant-administered questions. The predominant side effects reported were uneasiness, pyrexia (fever), voice difference, vomiting, and headache. The side effects were started at 2-16 h postvaccination while it takes an average duration of 48-60 h to last. Analysis shows nonpresence of major and serious side effects makes the Covidshield vaccine safe for use in the COVID-positive history population.